Wet and Dry Deposition Fluxes of Polychlorinated Biphenyls (PCBs) in an Urban Area of Turkey - Gunindi, Manolya; Tasdemir, Yucel (SPRINGER INTERNATIONAL PUBLISHING AG, 2011)
Atmospheric polychlorinated bihenyls (PCBs) deposit by dry and wet deposition mechanisms, and therefore they constitute a significant polluting source for lands and surface waters. Various samplers have been used to determine the PCB pollution level resulting from deposition. In the presented study, a modified wet deposition sampler (WDS) was used for sampling both wet and dry deposition samples with the same instrument by which wet deposition reservoir of the WDS is opened and dry deposition reservoir is closed when rain starts. Wet and dry deposition samples were collected between June 2008 and June 2009. In the samples taken from BUTAL which is known as an urban area with heavy traffic, Sigma PCB dry deposition fluxes were determined as 18 +/- 10 ng/m(2) -day, and wet deposition fluxes for dissolved and particle phase were measured as 480 +/- 1,185 and 475 +/- 1,000 ng/m(2) -day, respectively. The dissolved and particle-phase PCB concentrations in rain were 10 +/- 13 and 13 +/- 14 ng/l, respectively. The contribution of wet deposition to total PCB deposition was determined as 52%. PCB concentrations in the ambient air were measured to be 370 +/- 200 and 20 +/- 20 pg/m(3) for gas and particle phases, respectively. Washout ratio was determined by proportioning rain concentration to concentration in air. The washout ratios of the samples were between 1,675-311,800 and 12,775-2,511,120 for dissolved and particulate phases, respectively.
Keywords: Atmospheric deposition; Concentration; Washout ratio; Wet deposition; Polychlorinated biphenyls; POLYCYCLIC AROMATIC-HYDROCARBONS; POLYBROMINATED DIPHENYL ETHERS; WATER-SURFACE SAMPLER; LAKE-MICHIGAN; AMBIENT AIR; GAS/PARTICLE CONCENTRATIONS; ORGANOCHLORINE PESTICIDES; ORGANIC-COMPOUNDS; TEMPORAL TRENDS; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources